Consumption of fruits and vegetables by types and sources across urban and rural Senegal - Faye, Ndeye Fatou; Fall, Talla; Reardon, Thomas; Theriault, Veronique; Ngom, Yacine; Barry, Mamadou Bobo; Sy, Mouhamed Rassoul (Emerald Publishing Limited, 2024)
This paper analyzes the consumption of fruits and vegetables (FV) in Senegal by: (1) urban and rural areas; (2) FV types (African-indigenous vs non-indigenous); (3) sources of FV (imports, purchases and own-production).The authors undertake descriptive and regression analyses on consumption of FV sourced from purchases, own-production and gifts. The data come from primary surveys in 2017/2018 of 6,328 rural and urban households in Senegal.The analysis showed that FV are important in urban and rural food consumption. A stunning 76% of rural FV consumption is from purchases, showing the importance of FV supply chains even into and among rural areas. Only 12% of national FV consumption is from imports. Most FV consumption in rural and urban areas is now of non-indigenous FV; African-indigenous FV have a minor share.A limitation of this paper is that it uses a cross-sectional dataset.There are few national survey-based studies of FV consumption in Africa. This is the first to disaggregate FV consumption between primary versus secondary cities and rural towns, and rural areas close to and far from cities, in such detail regarding types and sources of FV as outlined in the findings. The regressions contribute by including determinants beyond income, including gender, employment, spatiality and education.